Genome-Wide Identification of SNAC1-Targeted Genes Involved in Drought Response in Rice - Li, Xu; Chang, Yu; Ma, Siqi; Shen, Jianqiang; Hu, Honghong; Xiong, Lizhong (Frontiers in Plant Science, 2019)
Drought stress can cause huge crop production losses. Drought resistance consists of complex traits, and is regulated by arrays of unclear networks at the molecular level. A stress-responsive NAC transcription factor gene SNAC1 has been reported for its function in the positive regulation of drought resistance in rice, and several downstream SNAC1 targets have been identified. However, a complete regulatory network mediated by SNAC1 in drought response remains unknown. In this study, we performed Chromatin immunoprecipitation sequencing (ChIP-Seq) and RNA-Seq of SNAC1-overexpression transgenic rice (SNAC1-OE) lines and wild-type under normal and moderate drought stress conditions, to identify all SNAC1 target genes at a genome-wide scale by RNA-Seq analyses. We detected 980 differentially expressed genes (DEGs) in the SNAC1-OE lines compared to the wild-type control under drought stress conditions. By ChIP-Seq analyses, we identified 4,339 SNAC1-binding genes under drought stress conditions (SNAC1BGDs). By combining the DEGs and SNAC1BGDs, we identified 93 SNAC1-targeted genes involved in drought responses (SNAC1TGDs). Most SNAC1TGDs are involved in transcriptional regulation, response to water loss, and other processes related to stress responses. Moreover, the major motifs in the SNAC1BGDs promoters include a NAC recognition sequence (NACRS) and an ABA responsive element (ABRE). SNAC1-OE lines are more sensitive to ABA than wild-type. SNAC1 can bind to the OsbZIP23 promoter, an important ABA signaling regulator, and positively regulate the expression of several ABA signaling genes.